(untitled) (Dhaka University Law Journal, 2025)
The Parliament enacted the Contempt of Courts Act, 2013 repealing the Contempt of Courts Act, 1926. But the High Court Division (HCD) declared the Act unconstitutional in Asaduzzaman Siddiqui. This paper aims to evaluate the HCD’s decision on the basis of two scenarios: (i) the necessity of a new contempt law; and (ii) the contempt of court as a narrowly construed exception to the norm of freedom of expression. The Court declared several provisions (namely, sections 4, 5, 6, 7, 9, 10, 11 and 13(2)) of the Act ultra vires for violating articles 26(1), 27 and 108 of the Constitution. The present paper will show that comparable provisions of the Act exist in other jurisdictions, such as, in the UK and India. In such view of the matter, it is to hold that those provisions of the Act should not have been declared unconstitutional by the Court. The paper finds the view held by the Court convincing to the extent that section 10 and some sub-section/s of section 11 of the Act appear to be in conflict with the Constitution. However, the paper does not agree with the Court’s view that section 13(2) comes in conflict with the Constitution. The Court, as the paper would argue, committed an error of reasoning in holding sections 4, 5, 6, 7, 9 and 13(2) of the Act ultra vires the Constitution. The Court should have taken a much broader view of the freedom of expression and freedom of the press under article 39(2) of the Constitution. The objective of the paper if accomplished would help/guide the Court in striking the right balance between freedom of expression and contempt of court in our jurisdiction. Dhaka University Law Journal, 2024, 35 (1), 151-176